(3GdOjhGf GdehTMs - (3GdGgOd Gdjefj , MGJe Hf CMeO Hf ehSi GdGgOd GdMSjfj,J (B1013 (3g` s
(3ChdgG (B:s
(3CeMjG Ce MejG Ce bHS CjgG GdTeGS EfeG GdCMOGb CbOGMj hHS hGdeMjG cGS s
(3BNQgG (B:s
(3ZjH GdhLhO aGdTeS JWeS fhQ cd chcH hGNQb GdMOhO hdG JYLH aGdebGe CYLH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B151s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B228 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfI (B(3816) s
Keywords: (3GdCOHs